The Role of the Campus Environment in the Formation of Islamic Education Values - Isny Lellya; Akhmad Syahbudin; Juairiah Juairiah; Fatimah Az Zahra (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Character education based on Islamic values is a crucial aspect in the formation of students’ personalities, especially in vocational education environments with a semi-military system. The campus environment, encompassing physical, social, and cultural aspects, is believed to play a strategic role in the process of internalizing Islamic values. However, the extent to which these elements contribute to the Islamic behavior of students is still rarely studied in depth. This research aims to comprehensively analyze the impact of the campus environment on the internalization of Islamic educational values. The approach employed was qualitative descriptive, utilizing data collection techniques that included participatory observation and in-depth interviews with six final-year students, two lecturers, and two campus staff members. Data analysis was conducted thematically, through coding, categorization, and the identification of key themes that describe the relationship between the physical, social, and cultural aspects of the campus and the practice of Islamic values. The study’s results indicate a gap between the availability of worship facilities and religious programs, and the internalization of Islamic values in students’ daily behavior. Student participation tends to be formal and inconsistent, while semi-military discipline has not been fully integrated with the development of Islamic character. The social and cultural environment of the campus has not formed a collective culture that supports the practice of Islamic values as a whole. These findings confirm that strengthening Islamic educational values requires synergy between campus structure, social interaction, and culture, not just through the provision of formal facilities or programs. The implications of this research can serve as the basis for formulating a more effective Islamic character development strategy in semi-military vocational education.